2011
DOI: 10.1007/s00431-011-1588-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation and unusual clinical features in a patient with immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome

Abstract: Although IPEX syndrome is usually a disease of infancy, it should not be ruled out solely on the basis of age. IPEX presentation is so variable that it should be suspected in a male child with one or more autoimmune disorders and severe infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…Neonatal diabetes and nephrotic syndrome were reported as the only clinical features in the surviving 15-year-old patient with mutation V408M of FOXP3 [10]. IPEX was genetically proven in 11-year-old boy with diabetes, pure red cell aplasia, membranous glomerulopathy, and posterior reversible encephalopathy syndrome after a vaccination against influenza virus [22]. These atypical clinical presentations of IPEX indicated existing possible underestimation of the real morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal diabetes and nephrotic syndrome were reported as the only clinical features in the surviving 15-year-old patient with mutation V408M of FOXP3 [10]. IPEX was genetically proven in 11-year-old boy with diabetes, pure red cell aplasia, membranous glomerulopathy, and posterior reversible encephalopathy syndrome after a vaccination against influenza virus [22]. These atypical clinical presentations of IPEX indicated existing possible underestimation of the real morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Renal disease can be related either to autoimmunity or to prolonged administration of nephrotoxic drugs. They are generally described as tubulonephropathy (Kobayashi et al, 2001; Otsubo et al, 2011) and nephrotic syndrome (Gambineri et al, 2008; Rubio-Cabezas et al, 2009; An et al, 2011; Otsubo et al, 2011), although interstitial nephritis (Bindl et al, 2005; Patey-Mariaud de Serre et al, 2009; Moes et al, 2010) and membranous glomerulonephritis (Moudgil et al, 2007; Halabi-Tawil et al, 2009; Burroughs et al, 2010; Bae et al, 2011) have also been found in some patients’ histopathological examinations. A rare manifestation associated with the milder forms of IPEX with delayed diagnosis is arthritis involving one or more joints (Wildin et al, 2002; De Benedetti et al, 2006).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…В большинстве случаев IPEX-синдром дебюти-рует сразу после рождения или в течение первого года жизни пациентов [1,2,15]. Клинические про-явления IPEX-синдрома крайне вариабельны.…”
Section: Discussionunclassified
“…ПРОБЛЕМЫ ЭНДОКРИНОЛОГИИ, 5,2014 выявляются у детей старшего возраста [15,19]. Ауто-иммунный тиреоидит -вторая по частоте эндо-кринная патология у пациентов с IPEX-синдромом -чаще всего проявляется гипотиреозом [1].…”
Section: Discussionunclassified